Adsorption isotherm, kinetic and thermodynamic studies of activated carbon prepared from Garcinia mangostana shell. Issue 6 (12th March 2013) - Kang, Yee Li; Toh, Seong Khoon See; Monash, Purushothaman; Ibrahim, Shaliza; Saravanan, Pichiah
ABSTRACT In this study, Garcinia mangostana shell was used to prepare phosphoric acid activated carbon (GMAC). The adsorption studies of the GMAC were carried out using methylene blue as a model dye adsorbate and textile industry effluent. Adsorption studies were conducted in batch mode. Multiple variables affecting adsorption such as contact time, temperature and pH were studied. The optimum conditions for adsorption were found to be contact time of 60 min, temperature 323 K and pH 12. The resultant data were fitted into the Langmuir, Freundlich and Temkin isotherm. The data best fitted the Freundlich model indicating multilayer adsorption onto heterogeneous surface with irregular distribution of adsorption energy and affinity. The rate of adsorption has good correlation with pseudo‐second‐order kinetics, and diffusion models demonstrate that both film and intraparticle diffusion mechanisms are not the sole rate‐limiting step in this particular adsorption. An evaluation of thermodynamic parameters, namely ΔH°, ΔS° and ΔG°, indicates that the adsorption was feasible, spontaneous and endothermic in nature. The low values of ΔH° and ΔG° correspond to physical adsorption. The results reveal that GMAC can be successfully used to remove various types of dye from aqueous solution. © 2013 Curtin University of Technology and John Wiley & Sons, Ltd.